COMPANY SIZE AS A MODERATING VARIABLE OF THE INFLUENCE OF GREEN INNOVATION, ECO-EFFICIENCY, AND ENVIRONMENTAL PERFORMANCE ON CORPORATE VALUE. THE IMPACT OF GREEN INNOVATION, ECO-EFFICIENCY, AND ENVIRONMENTAL PERFORMANCE ON CORPORATE VALUE: THE MODERATING - Alya Yuliandari; Ela Widasari; Firda Mufidah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research seeks to examine how Green Innovation, Eco-Efficiency, and Environmental Performance shape Firm Value, with Firm Size functioning as a moderating variable. The population for this study consists of companies listed on the Indonesia Stock Exchange, with a selected sample of 100 observations. The data analysis methods employed include descriptive statistics and Moderated Regression Analysis (MRA). The results indicate that the constructed regression model meets the criteria for model validity with an Adjusted R-Square value of 27.3%. Empirical findings suggest that Firm Size significantly moderates the relationship by strengthening the positive effects of Green Innovation and Eco-Efficiency on Firm Value. However, Firm Size was found not to moderate the relationship between Environmental Performance and Firm Value. The conclusion of this study indicates that investors tend to place a higher value on green innovation and eco-efficiency in large-scale companies, while environmental performance is viewed as a standard obligation that is not influenced by firm size in the formation of market value.